The Southeastern Librarian, Vol.29, No.04, Winter 1979 - Tucker, Ellis E. (The Southeastern Library Association, 1979)
The Southeastern Librarian, Vol.29, No.04, Winter 1979. Periodical.
1 electronic record. 63 pages. Scanned from original document. Contents Include: Ellis E. Tucker- Editor's Page- 191, Helen D. Lockhart- From the President's Desk- 193, Letters to the Editor- 195, Elliot R. Horton- Nominating Committee Requests Help- 197, Charlotte Folk- The Researcher Researched: An Interview with Richard B. Harwell- 199, Ron Ecker- The Archives of Ancient Ebla- 207, Boyd Childress- Library History and College Catalogs- 210, Michael McDavid- Beyond Faculty Status: Creating a Library Constitution- 218, Ideas, Concepts, and Practices- 221, John David Marshall- Librarian's Bookshelf- 222, SELA Chronicle-231, Steven B. Schoenly- Index to Volume XXIX, 1979- 239, Index to Advertisers- 220
Keywords: Periodicals | Southeastern Library Association